Continuous in situ soil nitrate sensors: The importance of high‐resolution measurements across time and a comparison with salt extraction‐based methods. Issue 3 (5th May 2021) - Zhu, Yunjiao; Chen, Yuncong; Ali, Md. Azahar; Dong, Liang; Wang, Xinran; Archontoulis, Sotirios V.; Schnable, James C.; Castellano, Michael J.
Abstract: Soil NO3 – affects microbial processes, plant productivity, and environmental N losses. However, the ability to measure soil NO3 – is limited by labor‐intensive sampling and laboratory analyses. Hence, temporal variation in soil solution NO3 – concentration is poorly understood. We evaluated a new potentiometric sensor that continuously measures soil solution NO3 – concentration with unprecedented specificity due to a novel membrane that serves as a barrier to interfering anions. First, we compared sensor and salt extraction‐based measurements of soil NO3 – in well‐controlled laboratory conditions. Second, using 60 d of in situ soil NO3 – measurements every 10 s, we quantified temporal variation and the effect of sampling frequency on field estimations of mean daily NO3 – concentration both within and across days. In the laboratory, sensors measured soil NO3 – concentration without significant difference from theoretical adjusted soil NO3 – concentration or conventional salt extraction‐based methods. In the field, the sensors demonstrated no within‐day pattern in soil NO3 – concentration, although individual measurements within a day differed by as much as 20% from the daily mean. Across days, when soil solution NO3 – was dynamic (early spring) and sampling frequency was >5 d, estimates of mean daily NO3 – concentration were >20% from the actual mean daily concentration. In situ soil sensors offer potential to improve fundamental and applied sciences. However, in most situations, sensors will measure soil properties in a different manner than conventional salt‐extract soil sampling‐based approaches. Research will be required to interpret sensor measurements and optimize sensor deployment. Core Ideas: New sensors can measure soil NO3 − with similar accuracy as salt extract‐based methods. There was no diurnal pattern in soil NO3 − concentration. Within days, instantaneous NO3 − concentrations can vary by as much as 20% of the daily mean. Across days, sampling frequencies >5 d can result in poor estimation of mean daily NO3 − . Required sampling frequencies within and across days depend on season and plant growth.